PENGARUH PEMERIKSAAN DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK - ., Waluyo (Jurnal Ilmiah Binaniaga, 2012)
The role of taxes in National Revenue and Expenses Budget  continues to increase on all state revenues from year to year. The purpose of this study was to analyze the influences of the Tax Examination and Tax Billing in partially and simultaneously of the Tax RevenueObject in this research is the Tax Service Office Pratama Kosambi for the period 2008 – (Semester I) 2012. The sample was selected by Convenience Sampling Method. Data that use in this research is secondary data, such as Realization of Tax Examination, Target of Tax Examination,   Realization of Tax Arrears Disbursement, Amount  of Tax Arrears; Realization and Target of Tax Revenue for Income Tax, Value Added Taxes and / Sales Tax on Luxury Goods issued by the Tax Service Office.The results of this research are: (1) Tax Examination has significant influence to Tax Revenue, (2) Tax Billing has significant influence to Tax Revenue, (3) Tax Examination and Tax Billing simultaneously have significant influence to Tax Revenue.Keywords: Tax Examination, Tax Billing, Tax Revenue